Analisis Implementasi Google Meet Dalam Mendukung Pembelajaran Dalam Jaringan Di Masa Pandemi Covid-19 - Ihsanudin, Iman Ahmad; Najah, Titi Inayatun (Didaktika, 2021)
Online learning is a learning process by utilizing electronic tools and internet networks. The use of the right media in the online learning process can certainly make it easier for students to understand the subject matter. But the fact is that in online learning, educators only give assignments without direct delivery of material, due to the teacher's lack of understanding of technology, besides that educators and students are not used to carrying out online learning. So in this study, researchers will analyze the process of implementing Google Meet in supporting online learning during the covid-19 pandemic. Researchers used a qualitative approach and case study methods. the research site is at SD Muhammadiyah Serang City, the subject is homeroom teachers for grades 2A and 5, and students in grades 2A and 5 for the 2020/2021 academic year. The results of this study explain that: (1) the process of implementing Google Meet in online learning consists of 3 processes, namely planning, implementation and assessment or evaluation, (2) supporting factors, namely the availability of mobile phones, computers or laptops, sufficient quota, and good signal. good, and (3) the inhibiting factors are the unavailability of mobile phones, computers or laptops, insufficient quota, and poor signal. The conclusion of this study is that Google Meet has the potential and support to be used as an online learning medium during the Covid-19 pandemic.